TIBOLONE, AN ESTROGENIC PROGESTIN OF HORMONE REPLACEMENT THERAPY REDUCES COLONY FORMATION AND 3-DIMENSIONAL SPHEROID S-PHASE IN C6 RAT GLIOMA IN VITRO - Altinoz, M. A.; Bilir, A.; Ozpinar, A.; Baskan, O.; Elmaci, I. (OXFORD UNIV PRESS INC, 2018)
13th Meeting of the European-Association-of-Neurooncology (EANO), Stockholm, SWEDEN, OCT 10-14, 2018